Keeping the Faith: Religion, Positive Coping, and Mental Health of Caregivers During COVID-19 - Sen, Heera Elize; Colucci, Laura; Browne, Dillon T. (Frontiers in Psychology, 2022)
The COVID-19 pandemic has resulted in major stressors such as unemployment, financial insecurity, sickness, separation from family members, and isolation for much of the world population. These stressors have been linked to mental health difficulties for parents and caregivers. Religion and spirituality (R/S), on the other hand, is often viewed as promotive of mental health. However, the mechanisms by which R/S might promote mental health for parents during the pandemic remain unclear. Thus, this longitudinal study explores how R/S is associated with better caregiver mental health during the COVID-19 pandemic through higher levels of positive coping skills. A sample of N = 549 caregivers across Canada, the United States, the United Kingdom and Australia were recruited through the Prolific® research panel (67.8% female; age M = 41.33 years [SD = 6.33], 72.3% White/European). Participants were assessed on measures of psychological distress, coping, R/S, and COVID-19 disruption at three time points between May and November 2020. Cross-lagged panel analysis revealed that caregiver coping mediated the relationship between caregiver R/S and caregiver mental health. Findings highlight a mechanism through which R/S naturally conveys a mental health benefit during periods of social disruption, which may provide an important target for public health promotion and clinical intervention.